2017
DOI: 10.1002/hep.29465
|View full text |Cite
|
Sign up to set email alerts
|

Altered amino acid concentrations in NAFLD: Impact of obesity and insulin resistance

Abstract: Plasma concentrations of amino acids (AAs), in particular, branched chain AAs (BCAAs), are often found increased in nonalcoholic fatty liver disease (NAFLD); however, if this is due to increased muscular protein catabolism, obesity, and/or increased insulin resistance (IR) or impaired tissue metabolism is unknown. Thus, we evaluated a) if subjects with NAFLD without obesity (NAFLD-NO) compared to those with obesity (NAFLD-Ob) display altered plasma AAs compared to controls (CTs); and b) if AA concentrations ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
344
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(386 citation statements)
references
References 47 publications
(108 reference statements)
33
344
8
1
Order By: Relevance
“…This molecule's blood levels have higher predictive power of the disease than conventional diagnostics. In NAFLD and NASH patients in addition to phenylalanine, phenylacetate precursor, abundances of other amino acids, notably branched chain amino acids (BCAAs), are altered and associate with disease severity, suggesting that there may be other metabolites produced by microbiome that play role in the disease (Gaggini et al, 2018). Interestingly, mice chronically treated with phenylacetate feature elevated expression of genes related to fat metabolism (Lpl, Fasn), increased levels of hepatic triglycerides, and eventually developed liver steatosis (Hoyles et al, 2018).…”
Section: Phenylacetatementioning
confidence: 99%
See 1 more Smart Citation
“…This molecule's blood levels have higher predictive power of the disease than conventional diagnostics. In NAFLD and NASH patients in addition to phenylalanine, phenylacetate precursor, abundances of other amino acids, notably branched chain amino acids (BCAAs), are altered and associate with disease severity, suggesting that there may be other metabolites produced by microbiome that play role in the disease (Gaggini et al, 2018). Interestingly, mice chronically treated with phenylacetate feature elevated expression of genes related to fat metabolism (Lpl, Fasn), increased levels of hepatic triglycerides, and eventually developed liver steatosis (Hoyles et al, 2018).…”
Section: Phenylacetatementioning
confidence: 99%
“…Interestingly, mice chronically treated with phenylacetate feature elevated expression of genes related to fat metabolism (Lpl, Fasn), increased levels of hepatic triglycerides, and eventually developed liver steatosis (Hoyles et al, 2018). In NAFLD and NASH patients in addition to phenylalanine, phenylacetate precursor, abundances of other amino acids, notably branched chain amino acids (BCAAs), are altered and associate with disease severity, suggesting that there may be other metabolites produced by microbiome that play role in the disease (Gaggini et al, 2018).…”
Section: Phenylacetatementioning
confidence: 99%
“…Perturbations in microbial metabolism of AAAs and BCAAs and ensuing alterations in the serum metabolite profile have more recently been identified in NAFLD . Hoyles et al performed an integrated analysis of the gut metagenome, hepatic transcriptome, and serum and urine metabolomes in a cohort of women with obesity but without diabetes.…”
Section: Gut Microbial Metabolism In the Pathogenesis Of Nafldmentioning
confidence: 99%
“…(79) Perturbations in microbial metabolism of AAAs and BCAAs and ensuing alterations in the serum metabolite profile have more recently been identified in NAFLD. (70,132) Hoyles et al (70) performed an integrated analysis of the gut metagenome, hepatic transcriptome, and serum and urine metabolomes in a cohort of women with obesity but without diabetes. Compared to those without NAFL, women with NAFL had significant alterations in the gut metagenome, including differences in BCAA and AAA pathways, as well as in the serum metabolome.…”
Section: Amino Acid Biosynthesis and Metabolismmentioning
confidence: 99%
“…We read with interest the article of Gaggini et al reporting plasma concentrations of amino acids (AAs) in nonalcoholic fatty liver disease (NAFLD). (1) The researchers observed that patients with NAFLD had high levels of isoleucine and valine (branched-chain amino acids; BCAA), tyrosine, alanine, lysine, and glutamate. More specifically, the researchers found that BCAA correlated with alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels; therefore, they concluded that plasma levels of amino-transferases reflect increased transamination reactions, and that amino acids are markers of hepatic inflammation and fibrosis.…”
Section: To the Editormentioning
confidence: 99%